(untitled) (JOURNAL OF ADVANCES IN AGRICULTURE, 2017)
In Brazil, the natural occurrence of the species Lippia alba (Mill) N. E. Brown is broad and diffuse, which justifies a high phenotypic variation and the occurrence of several chemotypes. Furthermore, the molecular methods help to determine the genetic variability with greater precision, in relation to the morphological methods. Thus, the objective of this work was to evaluate the genetic variability of different genotypes of L. alba from the Metropolitan region of the State of Rio de Janeiro using ISSR markers. The experiment was conducted at the Institute of Agronomy of the UFRRJ, from twenty genotypes of L. alba. Thirteen ISSR primers were used, obtaining 97 amplified bands and 74 polymorphic bands, equivalent to 77.89% of the amplified bands. The dendrogram (Neighbor Joining) formed five groups and just the genotypes UFRRJ LA01 and UFRRJ LA02 were grouped by the same geographic region and chemotype. The lowest similarity was observed in the grouping that joined the accessions UFRRJ LA14 and UFRRJ LA06. These results confirm the genetic variation between the genotypes, even when originating from the same region. L. alba genotypes from the Metropolitan Region of Rio de Janeiro show genetic and phytochemical variability.